2013
DOI: 10.1152/ajpregu.00117.2013
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal plasticity in hibernation and the proposed role of the microtubule-associated protein tau as a “master switch” regulating synaptic gain in neuronal networks

Abstract: Arendt T, Bullmann T. Neuronal plasticity in hibernation and the proposed role of the microtubule-associated protein tau as a "master switch" regulating synaptic gain in neuronal networks. Am J Physiol Regul Integr Comp Physiol 305: R478 -R489, 2013. First published July 13, 2013 doi:10.1152/ajpregu.00117.2013.-The present paper provides an overview of adaptive changes in brain structure and learning abilities during hibernation as a behavioral strategy used by several mammalian species to minimize energy expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 206 publications
2
70
0
Order By: Relevance
“…We assume chronic exposure to cold environment might actually increase performance as it has been reported before (review: Palinkas, ). In summary, the cold temperature during hibernation does not affect spatial memory, which is consistent with the previous finding that after consolidation memory is more resistant (Andjus et al, ) than immediately after acquisition (Moser and Andersen, ) (review: Andersen and Moser, ; Arendt and Bullmann, ).…”
Section: Discussionsupporting
confidence: 92%
“…We assume chronic exposure to cold environment might actually increase performance as it has been reported before (review: Palinkas, ). In summary, the cold temperature during hibernation does not affect spatial memory, which is consistent with the previous finding that after consolidation memory is more resistant (Andjus et al, ) than immediately after acquisition (Moser and Andersen, ) (review: Andersen and Moser, ; Arendt and Bullmann, ).…”
Section: Discussionsupporting
confidence: 92%
“…This process is likely mediated by hyperphosphorylation of tau, a microtubule associated protein, but prolonged regression may lead to neuropathies, so arousal may serve to reverse temporarily the tau hyperphosphorylation and synaptic regression, minimizing neuronal damage in hibernators (reviewed in ref. 7).…”
Section: What "Causes" Arousals?mentioning
confidence: 99%
“…Phosphorylation of Tau is known to depend on body temperature, physiologically in hibernating mammals, and as a well-known complication of anesthesia (Arendt et al, 2003;Planel et al, 2007;Su et al, 2008;Run et al, 2009;Tan et al, 2010;Menuet et al, 2011bMenuet et al, , 2012Arendt & Bullmann, 2013). Preliminary measurements of body temperature in terminal Tau.P301L mice with a normal GSK3 background, or deficient in either GSK3 isozyme, revealed variable lowered core body temperatures in the terminal stages, ranging from nearly normal to as low as 22°C.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, our observations of the relationships between hypothermia in terminal Tau.P301L mice and the phosphorylation of Tau paralleled the phosphorylation of Tau in certain hibernating species. Most spectacular are hibernating arctic ground squirrels, which accumulate, in their central neurons, very high levels of phosphorylated tau that are fully reversible upon arousal (Arendt et al, 2003;Su et al, 2008;Stieler et al, 2011;Arendt & Bullmann, 2013). Simi- larly, in hypothermic terminal Tau.P301L mice, we found that raising their body temperature above 32°C reversed, although not completely, the hyperphosphorylation of Tau.P301L and, to a lesser extent, the level of insoluble Tau aggregates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation